Wild Chimpanzees Infected with 5 Plasmodium Species - Kaiser, Marco; Löwa, Anna; Ulrich, Markus; Ellerbrok, Heinz; Goffe, Adeelia S.; Blasse, Anja; Zommers, Zinta; Couacy-Hymann, Emmanuel; Babweteera, Fred; Zuberbühler, Klaus; Metzger, Sonja; Geidel, Sebastian; et al. (Emerging infectious diseases, 2010)
Despite ongoing and, in some regions, escalating morbidity and mortality rates associated with malariacausing parasites, the evolutionary epidemiology of Plasmodium spp. is not well characterized. Classical studies of the blood pathogens of primates have found protozoa resembling human malaria parasites in chimpanzees and gorillas (1); however, these studies were limited to microscopy, negating conclusions regarding evolutionary relationships between human and ape parasites. Recent studies that used molecular approaches showed that captive and wild chimpanzees (Pan troglodytes) and lowland gorillas (Gorilla gorilla), as well as captive bonobos (Pan paniscus), harbor parasites broadly related to P. falciparum (2–5); wild and captive gorillas and captive bonobos and chimpanzees are sometimes infected with P. falciparum itself (4–6). Further, captive chimpanzees and bonobos have been shown to have malaria parasites related to human P. ovale and P. malariae (6–8); P. vivax has been identified in various monkeys and 1 semiwild chimpanzee (5,9). Recently, P. knowlesi, a simian malaria species, became the fifth human-infecting species (10), highlighting the possibility of transmission of new Plasmodium spp. from wild primates to humans.
Keywords: Wild Chimpanzees; Plasmodium Species